Developing a theory based on the causes of technical debt injection into software projects in Colombia (2020)
Engineering, like sciences such as physics, seeks to ensure that the conclusions reached can be verified through experiments, and that subsequent theories allow predictions to be made in future observations. This procedure is applied in this article, whose objective is the identification of the causes that favor the injection or presence of technical debt, and its application in software projects in Colombia, to build a theory that allows explaining this behavior. In turn, these causes could be also extrapolated to physical research projects. Results showed that "focus on producing more at the expense of quality" is the most cited cause in general. Conversely, "planning and management" is the most cited category of causes of technical debt. The concept of technical debt is well understood by software practitioners and that most efforts need to be invested by researchers on offering strategies and tools to support technical debt management.